Hyperinsulinism: molecular aetiology of focal disease. Issue 5 (1st November 1998) - Ryan, F; Devaney, D; Joyce, C; Nestorowicz, A; Permutt, M A; Glaser, B; Barton, D E; Thornton, P S
Abstract : Persistent hypoglycaemia in infancy is most commonly caused by hyperinsulinism. A case is reported of the somatic loss of the maternal 11p in an insulin secreting focal adenoma in association with a germline SUR-1 mutation on the paternal allele in a baby boy with hyperinsulinism diagnosed at 49 days old. A reduction to homozygosity of an SUR-1 mutation is proposed as a critical part of the cause of focal hyperinsulinism.